INCREASING STUDENTS INTEREST IN LEARNING MATHEMATICS USING LEARNING MEDIA BASED ON MACROMEDIA FLASH 8 ON THE SUBJECT OF CUBES AND RECTANGULAR PRISM - Elida Fachriyati; Nur Arina Hidayati (Universitas Ahmad Dahlan, 2018)
This research aims to increase students' learning interest in mathematics using Macromedia flash professional eight media-based learning on the subject of cubes and rectangular prism on students class VIII B of SMP Muhammadiyah 1 Yogyakarta the academic year 2016/2017. The subjects of this research are students of class VIII B of SMP Muhammadiyah 1 Yogyakarta in 2016/2017. The object of this research is the mathematics learning process using Macromedia flash professional eight media-based learning. The techniques of data collection are observation and interview. The data are analyzed by qualitative descriptive analysis. This research is included in class action research consists of two cycles. The result of this research showed that Macromedia flash professional eight media-based learning can increase students' learning interest in the mathematics of class VIII B in SMP Muhammadiyah 1 Yogyakarta academic year 2016/2017. It can be seen from the result of the observation sheet about students’ learning interest in each cycle, which is the percentage of students’ learning interest in mathematics in cycle I is 55,06% with the criteria of enough and in cycle II was increased to 62,49% with the criteria of good. Moreover, each cycle's test result also increased, which can be seen from a test result in cycle I, which has 71,25, and in cycle II the mean was increased to 77,08.